Hasil Benih Kentang yang diberi Pembenah Tanah pada Perbedaan Waktu Panen - Dian Krisdayani Dewi; Linlin Parlinah; R. Budiasih; Lia Amalia (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2022)
This article aims to determine the effect of the dose of soil dressing enriched with Phosphate solubilizing bacteria on the difference in harvest time on the yield of potato seeds. The environmental design used was a Randomized Group Design (RGD), there were nine treatments and each treatment was repeated 3 times. The combination of treatments tested as follows: A= control harvested at the age of 90 DAP, B= control harvested at the age of 100 DAP, C= control harvested at the age of 110 DAP, D= soil reformer 10 tons ha-1 in harvest 90 DAP, E= soil reformer 10 tons ha-1 harvested 100 DAP, F= soil reformer 10 tons ha-1 harvested 110 DAP, G= soil reformer 20 ha-1 harvested 90 DAP, H= soil reformer 20 tons ha-1 harvested 100 DAP and I= soil reformer 20 ha-1 harvested 110 DAP. The results showed that the administration of various doses of soil reformers that had been enriched with PSB was able to increase plant height, number of leaves, number of planting tubers and weight of planting tubers when compared to controls. The best response was shown from a dose of soil dressing treatment of 10 tons of ha-1 at harvest time of 100 DAP.